Field-induced transformations in the biaxial order of non-tilted phases in a bent-core smectic liquid crystal - PANARIN, YURI PETROVICH; NAGARAJ, MAMATHA; VIJ, JAGDISH KUMAR (Institute of Physics, 2010)
The structural and electro-optic investigations of an achiral bent-core molecule in SmAPA phase, in which the polar directors in the neighboring layers are arranged anti-ferroelectrically, show that it undergoes transformation from one biaxial to another biaxial structure via a quasi-stable uniaxial structure on the application of the electric field. The non-continuous change in biaxiality is explained by an intermediate state in which the secondary directors in the neighboring layers are perpendicular to each other.
PUBLISHED
Keywords: Condensed matter physics; Soft matter, liquids and polymers